2022
DOI: 10.1039/d2nr02273g
|View full text |Cite
|
Sign up to set email alerts
|

An acceptor-shielding strategy of photosensitizers for enhancing the generation efficiency of type I reactive oxygen species and the related photodynamic immunotherapy

Abstract: Developing efficient photosensitizers (PSs) that can generate Type I reactive oxygen species (ROS) under illumination, is considered an effective way to improve photodynamic therapy (PDT) outcomes due to the hypoxic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This demonstrated that the connection of the styrylpyridine cation could enhance the ICT between the strong donor TPA and the intermediate acceptor benzothiadiazole. The emission peaks of TPA-N- n ( n = 4/8/12) were similar to each other, which demonstrated that the existence of alkyl side chain could only affect the molecular conformation, not the electron distribution. , …”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…This demonstrated that the connection of the styrylpyridine cation could enhance the ICT between the strong donor TPA and the intermediate acceptor benzothiadiazole. The emission peaks of TPA-N- n ( n = 4/8/12) were similar to each other, which demonstrated that the existence of alkyl side chain could only affect the molecular conformation, not the electron distribution. , …”
Section: Resultsmentioning
confidence: 55%
“…In general, chromophores with typical electron donor–acceptor (D–A) structures were beneficial to red-shift absorption/emission wavelength and generate ROS upon photoirradiation. ,, Inspired by this principle, a series of D–A molecules with a distinct length of the alkyl chain, named TPA-N- n ( n = 4/8/12), were successfully synthesized (Scheme ). The twisted triphenylamine (TPA) structure as the electron donor could work as a rotor to regulate the movement of molecules in the aggregated state.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations